High‐fidelity simulation in training dental students for medical life‐threatening emergency. (23rd August 2017) - Roy, E.; Quinsat, V. E.; Bazin, O.; Lesclous, P.; Lejus‐Bourdeau, C.
Abstract: Introduction: Any dental surgeon may be faced with a critical life‐threatening emergency situation. In our university, all students in dentistry receive a standard course on emergency first aid. The aim of this prospective, comparative, single‐centre study was to determine whether additional training on a high‐fidelity patient simulator would improve student performance. Methods: After approval by an Ethical Committee and written informed consent, the students of the Simulation group (n=42) had full‐scale high‐fidelity training on a patient simulator SimMan 3G ™ (3 hours by six students). They participated in pairs in two scenarios (airway obstruction, seizures, allergies, vasovagal syncope, asthma, chest pain). The first scenario was simple, and the second was a progression to cardiac arrest. Three months later, the Simulation group and the Control group (n=42) participated in a test session with two scenarios. The primary end point was the score at the test session (with a standardised scoring grill, direct observation and audio‐video recording). Data were median and 25%‐75% percentiles. Results: High‐fidelity training strongly improved the score on the test obtained by the students of the Simulation group (146 [134‐154]) which was much higher ( P <.0001) than in the Control group (77 [67‐85]). Technical as well as non‐technical skills components of the scores were improved. In addition, performances of the Simulation group were increased between the training and the test. Simulation session was very positively assessed by the students. Conclusions: The results support the systematic introduction of training to critical life‐threatening emergency situations on high‐fidelity patient simulators the dentistry curriculum. The impact on clinical practice in the dental office remains to be assessed.